Factors associated with personal protective equipment use among agricultural pesticide handlers in Samarahan, Sarawak, Malaysia: a cross-sectional study - Zaidani Ekram, Attamimi; Lim, Siong Huei; Sam Froze, Jiee (Springer Nature, 2026)
Introduction Personal protective equipment (PPE) mitigates pesticide harm, but adherence remains inconsistent among smallholder farmers. We estimated the prevalence of full PPE use and identified associated factors among agricultural pesticide handlers in Samarahan, Sarawak using the Health Belief Model (HBM). Methods A cross-sectional survey of 297 farmers who handled pesticides within the past six months was conducted using interviewer-administered questionnaire on sociodemographic, knowledge and HBM constructs. Logistic regression with purposeful selection examined factors associated with full PPE use. Results Full PPE adherence was 17.2% (51/297). Most clothing items were widely used, while ocular and face protection were lowest (goggles 39.1%; face shield 27.3%). Younger age (aOR = 0.887 per year increase, 95% CI [0.839, 0.938], p < 0.001) and more farming years (aOR = 1.046, 95% CI [1.006, 1.088], p = 0.024) were associated with full PPE use. Among HBM constructs, higher perceived susceptibility and severity (aOR = 2.618; 95% CI 1.571, 4.365; p < 0.001) and cues to action (aOR = 2.665, 95% CI [1.499, 4.740], p < 0.001) increased odds, whereas perceived barriers decreased the odds (aOR = 0.529, 95% CI [0.355–0.790], p = 0.002). Perceived benefits showed an unexpected inverse association, possibly reflecting competing discomforts or practical barriers to comprehensive PPE use (aOR = 0.303, 95% CI [0.100, 0.921], p = 0.035). Conclusion Full PPE use was uncommon with ocular and face protection notably underused. Factors clustered around threat appraisal, cues and barriers alongside age and experience, illustrating operation of HBM in smallholder tropical agriculture. Findings provided a baseline for targeted training, prompts and barrier-reduction strategies in Sarawak.